Faktor Faktor yang Mempengaruhi Motivasi Pajak Terhadap Kebijakan Transfer Pricing pada Perusahaan yang Terdaftar di Bursa Efek Indonesia (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
Transfer pricing is a tool used by companies to control the company's business activities. The purpose of this study was to analyze the factors influencing tax motivation on company policies in conducting transfer pricing. This study uses secondary data obtained from the company's annual audited financial statements, then analyzed using the Statistical Package for Social Sciences (SPSS) program. The results of this study indicate that tax motivational factors are: tax expense, tax planning, leverage and exchange rates that have different influences on the company's transfer pricing policy. Tax expense, tax planning and leverage have a positive influence on company policies in transfer pricing, while exchange rates have a negative influence on the company's policy of transfer pricing.